Biodegradability of organic matter associated with sewer sediments during first flush. - Sakrabani, Ruben; Vollertsen, Jes; Ashley, Richard M.; Hvitved-Jacobsen, Thorkild (Elsevier, 2009)
The high pollution load in wastewater at the beginning of a rain event is commonly known to originate from the erosion of sewer sediments due to the increased flow rate under storm weather conditions. It is essential to characterize the biodegradability of organic matter during a storm event in order to quantify the effect it can have further downstream to the receiving water via discharges from Combined Sewer Overflow (CSO). The approach is to characterize the pollutograph during first flush. The pollutograph shows the variation in COD and TSS during a first flush event. These parameters measure the quantity of organic matter present. However these parameters do not indicate detailed information on the biodegradability of the organic matter. Such detailed knowledge can be obtained by dividing the total COD into fractions with different microbial properties. To do so oxygen uptake rate (OUR) measurements on batches of wastewater have shown itself to be a versatile technique. Together with a conceptual understanding of the microbial transformation taking place, OUR measurements lead to the desired fractionation of the COD. OUR results indicated that the highest biodegradability is associated with the initial part of a storm event. The information on physical and biological processes in the sewer can be used to better manage sediment in sewers which can otherwise result in depletion of dissolved oxygen in receiving waters via discharges from CSOs.
Keywords: Biodegradability; First flushes; Organic matter; Watercourse; Oxygen utilisation rate (OUR); Combined Sewer Overflow (CSO)